Effects of traditional soil management practices on the nutrient status in Sahelian sandy soils of Niger, West Africa - Suzuki, K.; Matsunaga, R.; Hayashi, K.; Matsumoto, N.; Tabo, Ramadjita; Tobita, S.; Okada, Kensuke (Elsevier, 2014)
In the Fakara region of the Sahel zone, Niger, West Africa, farmers have been implementing traditional soil man-agement practices such as the application of dry farmyard manure (FYM) and household waste (HHW), livestockcorralling, and fallows. Previousstudies, however, have not accumulatedenough data onthe effects of theseprac-tices on the soil nitrogen (N) pool in the Sahelian sandy soils.The objectives of this study were to evaluate the effects of these traditional practices on each N pool and on othernutrients. As the indicator of available N, phosphate buffer extractable organic nitrogen (PEON) was employed.Total N was significantly higher in thefields adjacent to houses (H) and suburbanfields where FYM had been ap-plied for 10 years (FYM10) or 5 years (FYM5), compared with that in the no-treatmentfields (NT) which had re-ceived no organic matter (OM) and chemical fertilizer for several decades. FYM10, H, and reserved fallows (RF)showedsignificantlyhigher levelsofPEONthan ofNT. The amounts of totalN and PEONinsoils from allcorrallingpractices, and all normal fallows were at the same level compared with NT. Similarly, the mineral N pool washigher for the soils from H, FYM10, and mixed corralling with sheep and goats.The principal component analyses (PCA) showed that all eigenvalues of soil pH, exchangeable potassium (K),available phosphorus (P), total N and carbon (C), PEON and mineral N in principal component 1 (PC1) were pos-itive, thus relating strongly to soil management practices which can enhance the essential nutrients: the pool ofN, P, and K, and C pool in soil. For PC2, the eigenvalues of mineral N, exchangeable K, and pH were positive,strongly relating to soil management practices which can enhance cations in soil. In comparison with NT theeigenvalues of PC1 of the managements with OM application were higher than in NT while those for the normalfallows without OM application were as low as those in NT. The eigenvalues of PC2 were higher for H and all cor-ralling practices compared with the values for NT. We understood that the practices of transporting manure andcorralling are important for the improvement of the fertility of Sahelian soils. Furthermore, thefindings suggestthat corralling is a more economical and useful practice than the others; livestock are moved around and dropmanure directly on the farmland, thus the loss of OM in transportation and the labor requirement are also low